Development and application of a chemical desorption method for determination of BTEX in ambient air from gas stations using gas chromatography - Luciano Guedes dos Santos, Gil; Sena Gomes Teixeira, Leonardo (Seven Editora, 2023)
Air pollution has caused damage to human health resulting from simple irritations and morbidity in the work to the development of cancer. An analytical method was developed to determination of benzene, toluene, ethylbenzene, m-xylene, p-xylene and o-xylene (BTEX) concentrations in samples of ambient air of gas stations by active sampling on adsorbent tubes containing activated charcoal followed by chemical desorption and analysis by gas chromatography with flame ionization detector. Tests were done using various solvents in order to verify the recovery rate (RR) of each one of them. So, tests indicated that dichloromethane presented the best results of RR, with values above 75% of extraction of BTEX compounds. Sampling was performed in ambient air of gas stations located in Amargosa city in Bahia. The concentrations found in ambient air from gas stations ranged from 16.9 to 44.5 μg m-3 for benzene; 39.9 to 247 μg m-3 for toluene; 15.6 to 29.4 μg m-3 for ethylbenzene; 12.7 to 68.5 μg m-3 for m-xylene; 13.7 to 63.3 μg m-3 for p-xylene and 13.0 to 42.2 μg m-3 for o-xylene. The results obtained in this proposed method were compared with the results obtained in a comparative method using thermal desorption and showed no significant differences, confirming the validity of the method. The concentrations of the compounds found in this study are classified not carcinogenic to humans by RN (Regulatory Norm) - 15 from the Ministry of Labour and Employment in Brazil, with the exception of benzene.DOI: https://doi.org/10.56238/devopinterscie-177